Situation Report: Bulgaria, 3 January 1974 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Closer Contacts between Bulgarian and Soviet Journalists' Unions Decree on Better Utilization of Private Plots More on Energy Problems in Bulgaria Diplomatic Relations with West Germany Established